Pengelolaan Perubahan di Bidang Pelayanan Publik: Langkah Normatif Penyiapan Aparatur Pemerintah Daerah Untuk Melakukan Perubahan - Enni Iriani (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
Bureaucracy and public service reforms require competent and innovative government apparatur who are ready to change. Nowadays, we are wondering whether the government has initiatives to prepare its apparaturs for the reforms. Has the government anticipated both the obvious and hidden rejections from its apparatus./ what acts should the government take to get its appaaratus ready for the reforms? The paper intends to propose some practical steps for the government to take in order to manage and lead its apparatus in this pressuring times.